1987
DOI: 10.1029/jd092id11p13231
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ozone distribution in the stratosphere from far‐infrared observations

Abstract: The distribution of isotopically heavy ozone in the stratosphere has been obtained from an analysis of balloon-based high-resolution thermal emission spectra in the far infrared. The mixing ratio profiles of 160160180 and 160180160, retrieved from inversion of several limb sequences of a number of spectral lines in the 39-76 cm -• region, indicate enhancements over the expected values in the 25-to 37-km altitude range. The ratio of total heavy isotopic ozone 500 3 to normal '•80 3 shows enhancements of •45% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Since the discovery over 30 years ago, these findings have been confirmed by further mass spectrometer measurements of atmospheric samples (Krankowsky et al, 2007), and by high-resolution spectroscopy using surface-based total-column measurements (Rinsland et al, 1985;Meier and Notholt, 1996), balloon-borne instruments (Abbas et al, 1987;Goldman et al, 1989;Johnson et al, 2000;Haverd et al, 2005), and space-based spectrometers (Irion et al, 1996;Piccolo et al, 2009;Sato et al, 2014). Laboratory research indicated that the observed isotopic enrichment is primarily controlled by unusually strong isotope effects associated with the O 3 formation reaction (Morton et al, 1990):…”
Section: Introductionmentioning
confidence: 63%
“…Since the discovery over 30 years ago, these findings have been confirmed by further mass spectrometer measurements of atmospheric samples (Krankowsky et al, 2007), and by high-resolution spectroscopy using surface-based total-column measurements (Rinsland et al, 1985;Meier and Notholt, 1996), balloon-borne instruments (Abbas et al, 1987;Goldman et al, 1989;Johnson et al, 2000;Haverd et al, 2005), and space-based spectrometers (Irion et al, 1996;Piccolo et al, 2009;Sato et al, 2014). Laboratory research indicated that the observed isotopic enrichment is primarily controlled by unusually strong isotope effects associated with the O 3 formation reaction (Morton et al, 1990):…”
Section: Introductionmentioning
confidence: 63%
“…See IUPAC [1983].) Further stratospheric enrichment of 500 3 has been reported based on mass spectrometry [Mauersberger, 1987], far-infrared emission spectroscopy [Abbas et al, 1987;Carli and Park, 1988], and cryogenic grab-sampling followed by mass spectrometry [Schueler et al, 1990] Table 1 [1986] reported good model fittings to their laboratory spectra, such laboratory measurements would probably produce a constant, corrective scaling of the line intensities (though not necessarily the same amount for both isotopomers), and would not affect the precision of the enrichments described here.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past ten years evidence for a non-mass dependent enhancement of 49 Οβ and 50 O3 relative to 48 Οβ in stratospheric ozone has been continually mounting (39)(40)(41). The degree of enhancement appears to increase with altitude with maximum values of about 40% being reported.…”
Section: Relationship To Heavy Ozone Productionmentioning
confidence: 85%